Temperature Dependence Study of Chiral Ether Derivative by 1H NMR Relaxation Time - Ekinci, Arzu; Zafer Koylu, M.; Askin, Muzaffer (Asian Journal of Chemistry, 2014)
Measurement of spin-lattice relaxation time T1 has been studied for the N-benzil-2-isobutyl aza-15-crown-5 ether derivative as a function of temperature. The data suggest that the underlying mechanism of relaxation rates is due to magnetic dipole-dipole interaction which is the dominant mechanism for the increase in temperature due to increase in the dipolar relaxation mechanism and, modulated by whole molecular tumbling. From ln T1 versus 1/T graph, activation energies (Ea) and correlation times (tc) were obtained.